Study on Shear Characteristics and Ultimate Bearing Capacity of Calcareous Silt Solidified by Fluorogypsum-Slag-Based Binders - Cheng, Tengqin; Dai, Wenting; Zhang, Renchao; Liu, Yunxiao (Journal of Progress in Civil Engineering, 2025)
Calcareous silt exhibits a higher concentration of calcium carbonate. Due to its inherently inferior engineering properties, calcareous silt necessitates solidification treatment prior to utilization. The shear strength of calcareous silt serves as a pivotal metric for evaluating the calcareous silt’s capacity to withstand shear deformation, which is of paramount importance for assessing soil stability and engineering performance. To explore the engineering properties of calcareous silt solidified with a fluorgypsum-slag-based(F) binders, this research utilized such an agent to solidify calcareous silt. Direct shear tests were subsequently conducted on the solidified calcareous silt samples to analyze the shear behavior of the silt at varying curing durations and solidifying agent dosages. numerical simulations of the ultimate bearing capacity of foundations were carried out using the Abaqus numerical modeling software. The experimental findings reveal that the F group possesses superior shear characteristics compared to cement group, with a 28-day cohesion value of 1365.36 KPa and a friction angle of 39.62° for the F20 cohort. The F group exhibits a tendency towards brittle failure influenced by aging and dosage, whereas the cement group demonstrates plastic failure traits. The rate of cohesion enhancement in the F group diminishes with aging but escalates with increased dosage. Numerical simulations indicate that the F group exhibits a notably higher ultimate bearing capacity of 5460.75 KPa, underscoring its excellent engineering efficacy.